Effect of boundary element details on the seismic deformation capacity of structural walls. - Oh, Young-Hun (Earthquake engineering & structural dynamics.)
The objective of this study is to investigate the effect of boundary element details of structural walls on their deformation capacities. Structural walls considered in this study have different sectional shapes and/or transverse reinforcement content at the boundaries of the walls (called boundary element details hereafter). Four full scale wall specimens (300 mm (hw) x 1500 mm (lw) x 200 mm (T) ) were fabricated and tested. Three specimens are rectangular in section and the other specimen has a barbell shaped cross section ( a wall with boundary columns). The rectangular wall specimens are reinforced according to the common practice used for reinforced concrete residence buildings in Korea and Chile. In this study, the primary variable for these rectangular specimens is the content of transverse reinforcement to confine the boundary elements of a wall. The barbell shaped specimen was designed in compliance with ACI 318-95. The response of the barbell shaped specimen is compared with those of other rectangular specimens. The effective aspect ratio of the specimens is set to two in this study. Based on the experimental results, it is found that the deformation capacities of walls, which are represented by displacement ductility, drift ratio and energy dissipation capacities, are affected by the boundary element details.